Selective H2 production from methanol over Rh/CoCMs nanocomposite at subzero ambient temperatures - Huanyu Yu; Xiaohong Liu; Shichao Zhang; Yanlan Wang; Yingping Huang; Xiang Liu (Chemical Engineering Journal, 2026)

The sustainable conversion of organophosphorus pollutant into nitrogen-doped porous carbon for 3-aminophenol degradation - Chunhong Zhou; Jiang Zhao; Xiaohong Liu; Huanyu Yu; Yanlan Wang; Qiuyan Li; Xiang Liu (Journal of Environmental Chemical Engineering, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

A mechanistic perspective: How does tert-butylhydroquinone retain antioxidative efficacy in edible oils during storage? - Mengqi Xu; Yaxing Yu; Jun Li; Yanlan Bi; Jun Liu; Chenyu Fu (Food Chemistry, 2025)

CaFe-layered double hydroxide corn straw biochar reduced heavy metal uptake by Brassica campestris L. and Ipomoea aquatic F.: Rhizosphere effects and oxidative stress alleviation - Fangming Yu; Tiantian Gu; Jiayu Wei; Chijian Tang; Songying Li; Yuyuan Chen; Yanlan Su; Kehui Liu; Jiangming Ma; Xin Liang; Yi Li (Journal of Environmental Management, 2023)

Insights into the heavy metal adsorption and immobilization mechanisms of CaFe-layered double hydroxide corn straw biochar: Synthesis and application in a combined heavy metal-contaminated environment - Xin Liang; Yanlan Su; Xinnuo Wang; Chuntao Liang; Chijian Tang; Jiayu Wei; Kehui Liu; Jiangming Ma; Fangming Yu; Yi Li (Chemosphere, 2023)

A modified diatomite additive alleviates cadmium-induced oxidative stress in Bidens pilosa L. by altering soil microbial communities - Fangming Yu; Xin Liang; Yanying Li; Yanlan Su; Shuting Tang; Jiayu Wei; Kehui Liu; Jiangming Ma; Yi Li (Environmental Science and Pollution Research, 2023)

Consistent responses of microbial C and N metabolic processes to elevated CO2 across global terrestrial ecosystems - Jiahui Lin; Yanlan Huang; Haochun Zhao; Mengjie Yu; Weiqin Su; Huaihai Chen; Peng Leng; Jihui Li; Yu Luo; Yong Li; Zhongmin Dai; Jianming Xu (Journal of Soils and Sediments, 2022)

Elevated temperature shifts soil N cycling from microbial immobilization to enhanced mineralization, nitrification and denitrification across global terrestrial ecosystems - Zhongmin Dai; Mengjie Yu; Huaihai Chen; Haochun Zhao; Yanlan Huang; Weiqin Su; Fang Xia; Scott X. Chang; Philip C. Brookes; Randy A. Dahlgren; Jianming Xu (Global Change Biology, 2020)
We assessed the response of soil microbial nitrogen (N) cycling and associated functional genes to elevated temperature at the global scale. A meta‐analysis of 1,270 observations from 134 publications indicated that elevated temperature decreased soil microbial biomass N and increased N mineralization rates, both in the presence and absence of plants. These findings infer that elevated temperature drives microbially mediated N cycling processes from dominance by anabolic to catabolic reaction processes. Elevated temperature increased soil nitrification and denitrification rates, leading to an increase in N 2 O emissions of up to 227%, whether plants were present or not. Rates of N mineralization, denitrification and N 2 O emission demonstrated significant positive relationships with rates of CO 2 emissions under elevated temperatures, suggesting that microbial N cycling processes were associated with enhanced microbial carbon (C) metabolism due to soil warming. The response in the abundance of relevant genes to elevated temperature was not always consistent with changes in N cycling processes. While elevated temperature increased the abundances of the nirS gene with plants and nosZ genes without plants, there was no effect on the abundances of the ammonia‐oxidizing archaea amoA gene, ammonia‐oxidizing bacteria amoA and nirK genes. This study provides the first global‐scale assessment demonstrating that elevated temperature shifts N cycling from microbial immobilization to enhanced mineralization, nitrification and denitrification in terrestrial ecosystems. These findings infer that elevated temperatures have a profound impact on global N cycling processes with implications of a positive feedback to global climate and emphasize the close linkage between soil microbial C and N cycling.

Brain REST/NRSF Is Not Only a Silent Repressor but Also an Active Protector - Yangang Zhao; Min Zhu; Yanlan Yu; Linli Qiu; Yuanyuan Zhang; Li He; Jiqiang Zhang (Molecular Neurobiology, 2017)